Changes in quality of life following hypoglycaemia in adults with type 2 diabetes: a systematic review of longitudinal studies - Matlock, KA; Broadley, M; Hendrieckx, C; Clowes, M; Sutton, A; Heller, SR; de Galan, BE; Pouwer, F; Speight, J (Wiley, 2021)
AIM: To conduct a systematic review of published studies reporting on the longitudinal impacts of hypoglycaemia on quality of life (QoL) in adults with type 2 diabetes.